Effect of Changes in Land-Use Management Practices on Soil Physicochemical Properties in Kabe Watershed, Ethiopia - Assefa, Fikru; Elias, Eyasu; Soromessa, Teshome; Ayele, Gebiaw T (Air, soil and water research, 2020)
Change in land-use management practices such as cultivation of steep slopes, overgrazing, and no or limited fallow periods, and slope position affects the quality of soils. As a result, assessing soil physicochemical properties and subsequent implications on soil fertility is essential for understanding the influence of agro-ecosystem revolution on agricultural soil quality and efficiency. In this research, we assessed the effect of land-use management practices on selected soil properties under varying terrain slopes and with and without soil conservation measures in a highly disturbed landscape in the northern part of Ethiopia in 2016. Based on the result, for all slope positions considered—namely, lower (1%-15%), middle (15%-30%), and upper (30%-45% and above)—with and without soil conservation, soil moisture content, porosity, silt, and clay proportions were lower in the cultivated land compared with grazing and forestland-use units. Conversely, soil bulk density and the sand fraction were higher in the cultivated land than grazing and forestland units, relatively. Observing changes in a terrain slope position, sand content of forest, grazing, and cultivated land units increased from lower to upper slope position whereas silt and clay fraction generally showed a decreasing trend from lower to an upper slope positions. In all slope positions with and without conservation practice, cation exchange capacity, exchangeable K+, Ca2+, and Mg2+ showed a significant increase from cultivated land to grazing and then forestland. The mean value of pH and electrical conductivity of cultivated lands with and without soil conservation were significantly low in all slope categories. Summarizing the analysis of variance for selected soil chemical properties with different slope positions, except available phosphorous, all chemical properties considered in this study are statistically significant (P < .05). In summary, the result confirmed that soil properties were strongly influenced by terrain slope, land use, and changes in management practice. Consequently, to conserve soil resources, policymakers need to implement appropriate land conservation strategies based on land-use structure and slope variation.